The stars beneath our feet - Moore, David Barclay (Yearling, 2019)
Lolly is having a terrible time--his brother Jermaine got in a fight and then got shot. He doesn't know how to go on, but using the two giant bags of LEGOs his mom's girlfriend gave him, Lolly finds himself caught up in making a gigantic city--so big it goes outside his apartment. Then, he and his friend Vega get jumped by a few older guys, and Lolly will have to decide either to join a "crew" and get revenge, or find a different path.